NATIONAL PARKS: THE PARADISE OR PARADOX - DENG, JINYANG (ASEAN Journal on Hospitality and Tourism, 2007)
It is widely recognized that national parks are places set aside for the protection of the ecological integrity of the park environment itself, for scientific research and environmental education, and for tourism and recreational pursuits, among other things. However, national parks also face a myriad of vexing problems, including policy dilemma between use and protection, consumption inequity, etc. From a global perspective, with a strong focus on the United States and Canada, this paper discusses the paradoxical issues associated with national parks in their emerging, development, management and policies. Suggestions to resolve these paradoxes are also presented.